Validity of an inertial system to measure sprint time and sport task time: a proposal for the integration of photocells in an inertial system - Bastida Castillo, A.; Gómez Carmona, C. D.; Ortega, J. P.; de la Cruz Sánchez, E. (International Journal of Performance Analysis in Sport, 2017)
This study presents a proposal for the integration of photocell data (time) into an inertial system. We divert the signal emitted by the infrared cell (ChronoJump, Spain) towards the inertial device (WIMU PRO, RealTrack System, Almeria, Spain) by an ANT + transmitter to make a mark that is later visualised in S PRO software (RealTrack System, Almeria, Spain). The objective of this study is to show the validity of an inertial system to measure sprint and sport task time by integrating photocells into an inertial system. For this purpose, we compared the time of 108 runs (at 20, 150 and 400 m) between inertial software and photocell software (gold standard). The results of the validity in this study were satisfactory and had a bias .0006 ± .0018 s. To conclude, the time measurements between photocells and an inertial system using ANT + are accurate and the proposal presented in this manuscript could make this sport activity monitoring more efficient.